RECONSTRUCTING STUDENT EXPERIENCES TO INCREASE ENTREPRENEURIAL INTEREST IN HIGHER EDUCATION - Rika Verawati; Mohd. Rafi Yaacob, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
Students' entrepreneurial experiences in higher education are becoming an increasingly important topic in the context of education and career development. Entrepreneurship in higher education involves the development of business ideas and a deep learning process about innovation, risk-taking, and practical resource management. The study method used is a qualitative approach, using in-depth interview techniques with several university students who are definitely young entrepreneurs. The data collected was analyzed using a thematic approach to identify patterns and variations in entrepreneurial experience development strategies. shows that students use a variety of cognitive and social decisions in reconstructing their entrepreneurial experiences, including reflection, collaborative learning, and mentoring. The findings of this study investigate how student entrepreneurial experience can increase students' ability to carry out entrepreneurship in a college environment. Efforts that have been made by students include the formation of business incubators, marketing facilities, product quality, courses, own abilities, convenience, and entrepreneurship programs. The conclusions of this study validate the importance of an integrated approach to supporting student entrepreneurial development in higher education with a curriculum approach and related support. This research contributes significantly to our understanding of how university students can optimize their entrepreneurial experience to prepare for their future as young entrepreneurs. ,, ,